The Influence of Sports on Executive Functions in Para-Athletes: A Pilot Study (Global Journal of Human-Social Science, 2025)
Sports practice can enhance both the physical and psychological abilities of individuals, including executive functions, which may influence other daily activities. This study aims to explore the correlation between sports and executive functions, considering the heterogeneity of results found in existing literature. The present pilot study focused on professional parasports athletes and used the Five-Digit Test (FDT) to measure and compare cognitive performance. This is a cross-sectional study conducted with ten (10) participants, five (5) of whom were elite athletes and five (5) from a sedentary population with disabilities. The results revealed a significant difference in performance between the two groups, particularly in the controlled processes of choice and task-switching. This statistical variation may suggest a potential enhancement in higher-order cognitive functions among the athlete group.
Keywords: para-athletes; executive functions; decisionmaking; cognitive flexibility